2022
DOI: 10.3390/biology11111578
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Analysis of Medicinal Plant Utilization among the Four Ethnic Communities in Northern Regions of Jammu and Kashmir, India

Abstract: Medicinal plants are utilized around the globe for the treatment of a wide range of ailments. This study is an attempt to document the utilization of medicinal plants across the four different cultural groups residing in the rural and remote villages of the northern districts of the Union territory of Jammu and Kashmir, India. To gather information related to medicinal plants and health care practices among the local folk, field surveys were conducted from February 2018 to May 2021. The ethnomedicinal informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Haq et al (2021) Ladakh region andAziz et al (2020) from the Pakistan Himalayas conducted a similar cross-cultural analysis and concluded that ethnicity and cultural practices have shaped traditional herbal knowledge among the local inhabitants Abidin et al (2021). from southwest Pakistan revealed similar findings, which confirm our findings from the Kashmir Himalayan region Mir et al (2022). also conducted a similar study in the northern regions of Jammu and Kashmir, India.…”
supporting
confidence: 83%
“…Haq et al (2021) Ladakh region andAziz et al (2020) from the Pakistan Himalayas conducted a similar cross-cultural analysis and concluded that ethnicity and cultural practices have shaped traditional herbal knowledge among the local inhabitants Abidin et al (2021). from southwest Pakistan revealed similar findings, which confirm our findings from the Kashmir Himalayan region Mir et al (2022). also conducted a similar study in the northern regions of Jammu and Kashmir, India.…”
supporting
confidence: 83%
“…Ethnoveterinary medicine is a system that is based on folk beliefs, conventional knowledge skills, methods and practices used for remedial diseases that maintains proper health of animals. It provides the chief source for the treatment of various disorders in livestock all over the world even today (Mir et al 2021(Mir et al , 2022. Man has used plant recipes for the curing of different diseases in their domesticated animals since the advent of human civilization (Khan et al 2021;Singh et al 2011;Rehman et al 2023;Ullah et al 2022;Abdin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Among them the species Oxalis carniculata represented with (91.8), and the second high calculated value was documented for Fumaria indica (91), and the third were Datura innoxia with (90) calculated value. The approached of fidelity level (FL) specifies the best curing ability of plant taxa against various specific disorder and having similarities with previous work of (Giday et al 2003;jan et al 2022a;Mir et al 2022c).…”
Section: Discussionmentioning
confidence: 99%